Merkel Cell Polyoma Viral Load and Intratumoral CD8+ Lymphocyte Infiltration Predict Overall Survival in Patients With Merkel Cell Carcinoma - von der Grün, Jens; Winkelmann, Ria; Meissner, Markus; Wieland, Ulrike; Silling, Steffi; Martin, Daniel; Fokas, Emmanouil; Rödel, Claus; Rödel, Franz; Balermpas, Panagiotis (Frontiers in Oncology, 2019)
Introduction: Merkel cell carcinoma (MCC) is linked to the presence of clonally integrated Merkel cell polyomavirus (MCPyV) in up to 80% of the cases. The aim of the study was to determine the prognostic value of baseline MCPyV viral load and lymphocytic infiltration. Methods: MCPyV DNA prevalence, integration status and viral load were determined by specific quantitative real-time PCR in surgical specimens obtained from 49 patients with MCC treated with (n=22, 45%) or without postoperative radiotherapy (RT). CD8+ tumor infiltrating lymphocytes (TILs) and programmed death ligand 1 (PD-L1) status were assessed using immunohistochemistry. MCPyV characteristics and immune marker expression were correlated with clinicopathological factors and overall survival (OS). Results: Median age at diagnosis was 74 (range, 42-100); 51% of the patients were female. One-, three, and five-year OS rates were 83.8%, 58.6% and 47.1%, respectively. A positive MCPyV status was associated with female gender (p=0.042). Tumor localization (head/arms vs. trunk) positively correlated with PD-L1 status (p=0.011) and combined CD8/PD-L1 expression (p=0.038). Overall CD8+ infiltration was inversely associated with N-stage (p=0.048). Stromal TILs correlated significantly with both PD-L1 expression (p=0.010) and N-stage (p=0.037). A high viral load (>median) was significantly associated with worse OS (p=0.029) and high intratumoral CD8+ infiltration with improved OS for the entire cohort (p=0.045). Conclusion: These data provide important insight on the role of MCPy DNA viral load and TILs in the context of PD-L1 in patients with Merkel cell carcinoma. Future clinical studies should aim to explore the effect of PD-1/PD-L1 immune-checkpoint inhibitors in combination with existing radiotherapy approaches.